PENGARUH EFEKTIVITAS MANAJEMEN DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKUR DESA (STUDI KASUS DI DESA KALIKAYEN) - Ahwan Sholih; Amanah Amanah (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2018)
The Village Fund is a concrete form of state recognition of the origin of the village and the local authority of the village. Village Funds are expected to provide additional energy for the village in developing and empowering villages, towards a strong, advanced and independent village. This study examines the Village Fund in the Kalikayen Village. The reason for taking the location is referring to previous research which says that Kalikayen Village is a village in which the village fund management is in accordance with the rules that apply in its management process. For this reason, the purpose of this study was to determine the relationship between Village Fund Management and the Level of Kalikayen Village Infrastructure Development. This analysis is carried out with a simple regression analysis method, with secondary data obtained from literature and primary data obtained from surveys, questionnaires and observations on the intended object. The results of statistical tests using SPSS generated data that the R Square test was found to be 0.471, this implies that the influence of the village fund management variable on the variable of infrastructure development was 47.2%. While the remaining 52.8% is explained by other unknown factors or variables in this study such as the enthusiasm of the residents, the leadership capacity of the village head, etc. Statistical test results prove that the village fund management variable (X) obtained sig value is 0.05 (0.005 <0.05). This means that the Hypothesis (Village Fund Management of Infrastructure Development) which states that village fund management has a positive and significant effect on infrastructure development is accepted.